The care cascade of chronic obstructive pulmonary disease in China: a cross-sectional study of individual-level data at enrolment into the national ‘Happy Breathing’ Programme - Wang, Chen; Qi, Weiran; Yang, Ting; Jiao, Lirui; Chen, Qiushi; Huang, Ke; Yu, Fengyun; Geldsetzer, Pascal; Bärnighausen, Till; Chen, Simiao (EClinicalMedicine, 2024)
Background - Understanding the chronic obstructive pulmonary disease (COPD) care cascade is crucial for identifying where and when to intervene to improve COPD outcomes. We aimed to determine the proportion of patients with COPD seeking care in China's health system who are lost at each stage of the COPD care cascade and how the patterns of loss vary across geographical regions and population groups. - Methods - From November 3, 2018, to April 22, 2021, we used individual-level patient data from the national Chinese ‘Happy Breathing’ Programme, which aims to identify patients with COPD and provide appropriate care. COPD was defined as a post-bronchodilator ratio of forced expiratory volume in 1 s to forced vital capacity (FEV1/FVC) <0.70. We calculated the proportions of individuals who, at enrolment into the ‘Happy Breathing’ Programme, (i) had ever undergone a pulmonary function test, (ii) had been diagnosed with COPD in the past, (iii) were currently on treatment for COPD, and (iv) had achieved control of their COPD. We examined the association between reaching each stage of the care cascade and individual patient characteristics as well as regional-level economic development and available resources in the health system using multilevel regression. - Findings - Among the 29,201 patients with COPD in the ‘Happy Breathing’ Programme, 41.0% (95% confidence interval [CI]: 40.4-41.6%) had ever been tested for COPD, 17.6% (95% CI: 17.1-18.0%) had previously been diagnosed with COPD, 8.5% (95% CI: 8.2-8.8%) were currently on treatment for COPD, 4.6% (95% CI: 4.3-4.8%) of patients had mild or no exacerbations in the prior year, and 3.9% (95% CI: 3.7-4.2%) of patients had suffered no exacerbations in the prior year. On average, patients living in the cities of Beijing, Wuhan, and Yinchuan had progressed further along the COPD care cascade than patients living in Daqing and Luoyang. Using multilevel regression, we found that young age, rural residence, and low regional per-capita GDP were significantly associated with larger losses at each stage of the COPD care cascade. - Interpretation - Substantial proportions of patients with COPD are lost at each stage of the COPD care cascade in the Chinese health system. The largest losses occur during the initial stages of the cascade, when diagnosis first occurs. New policies and interventions are required to boost COPD care, especially screening and diagnosis, in the Chinese health system to reduce this large disease burden. - Funding - This work was supported by Major Programme of National Natural Science Foundation of China (82090011), CAMS Innovation Fund for Medical Sciences (CIFMS) (2021-I2M-1-049), and Horizon Europe (HORIZON-MSCA-2021-SE-01; project number 101086139-PoPMeD-SuSDeV). TB was supported by the Alexander von Humboldt Foundation through the Alexander von Humboldt professorship award.